1998
DOI: 10.1097/00000658-199812000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy: Day-Care Versus Clinical Observation

Abstract: ObjectiveTo determine the feasibility and desirability of laparoscopic cholecystectomy (LC) in day-care versus LC with clinical observation. Summary Background DataLaparoscopic cholecystectomy has been performed regularly as outpatient surgery in patients with uncomplicated gallstone disease in the United States, but this has not been generally accepted in Europe. The main objections are the risk of early severe complications (bleeding) or other reasons for readmission, and the argument that patients might fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
133
1
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(161 citation statements)
references
References 17 publications
19
133
1
8
Order By: Relevance
“…The acceptability of same-day discharge has been reported in populations outside the UK, with satisfaction rates varying from 71-95%. 4,[17][18][19][20][21] In this study, 94% of patients were highly satisfied with the service we provided, both in the discharged and admitted groups. Sixteen significant intra-operative difficulties in 15 patients were encountered (Table 6).…”
Section: A B Introduction Of a Day-case Laparoscopic Cholecystectomy mentioning
confidence: 57%
See 1 more Smart Citation
“…The acceptability of same-day discharge has been reported in populations outside the UK, with satisfaction rates varying from 71-95%. 4,[17][18][19][20][21] In this study, 94% of patients were highly satisfied with the service we provided, both in the discharged and admitted groups. Sixteen significant intra-operative difficulties in 15 patients were encountered (Table 6).…”
Section: A B Introduction Of a Day-case Laparoscopic Cholecystectomy mentioning
confidence: 57%
“…Pain and nausea also appeared well controlled in our patients in comparison to published series. 4,11 To date, no authors have examined the burden on primary care providers after day-case LC. Our results indicate that 33% of patients contacted a healthcare professional within 14 days of surgery for an unplanned consultation.…”
Section: A B Introduction Of a Day-case Laparoscopic Cholecystectomy mentioning
confidence: 99%
“…6 In the era of day-surgery, several studies have shown that postoperative pain following successful laparoscopic cholecystectomy can be managed by regular oral analgesia. 7,8 In a study of 84 patients, Serralta et al 9 showed that the analgesic requirement following successful laparoscopic cholecystectomy is substantially less and opioids may not play a role in postoperative pain management.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost all patients who underwent the transthoracic procedure would choose the extensive procedure again. This is a remarkable result, because earlier studies (Keulemans et al, 1998;Nieuwkerk et al, 1998) showed that people tend to choose the treatment they have received, even if this treatment was randomly allocated. In the present study, patients apparently want to optimise the chances that the malignant disease is definitely cured.…”
Section: Clinicalmentioning
confidence: 99%
“…These choices are known as treatment preferences and typically involve informed patients Keulemans et al, 1998;Nieuwkerk et al, 1998;Awad et al, 2000). The treatment preference method is a realistic reflection of the actual decision situation.…”
mentioning
confidence: 99%